2015
DOI: 10.7324/japs.2015.501115
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hyperglycemic Effect of Tecomella undulata Extract by Ameliorating Pancreatic Dysfunction in Streptozotocin Induced Diabetic Albino Rats

Abstract: The primary objective of the present investigation is to evaluate the antihyperglycemic activity of the 50% ethanolic extract of the Tecomella undulata Seem. (TUE) bark in the streptozotocin induced diabetic rats. Methods: Single intraperitoneal injection (i.p.) of streptozotocin (60 mg/kg body weight) was used for induction of diabetes is wistar albino rats. The induction of diabetes was confirmed after 3 days after STZ injection and rats with fasting blood glucose levels greater than 200 mg/dl were considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Reitman and Frankel (1957) were suggested method for estimation of hepatic amino transferase enzymes which includes aspartate amino transferase (AST or SGOT) and alanine aminotransferase (ALT or SGPT). The serum total cholesterol (TC), triglyceride (TG), low density lipoproteins (LDL) and high density lipoproteins (HDL) concentrations were determined using commercial kits by enzymatic photocolorimetric methods (Das, et al, 2015) …”
Section: Biochemical Parametersmentioning
confidence: 99%
“…Reitman and Frankel (1957) were suggested method for estimation of hepatic amino transferase enzymes which includes aspartate amino transferase (AST or SGOT) and alanine aminotransferase (ALT or SGPT). The serum total cholesterol (TC), triglyceride (TG), low density lipoproteins (LDL) and high density lipoproteins (HDL) concentrations were determined using commercial kits by enzymatic photocolorimetric methods (Das, et al, 2015) …”
Section: Biochemical Parametersmentioning
confidence: 99%
“…According to the study's findings, 50% of the ethanolic extract exhibits considerable antidiabetic activity and a robust hypolipidemic potential in diabetic circumstances at various doses. (30) This research backs up our in-silico research that suggests quercetin and kaempferol, which have the lowest binding energies (-9.3 kcal/mol and -9.1 kcal/ mol, respectively) in complex with GKRP, may be useful in the treatment of diabetes. Regardless of the makeup of the phytoconstituents, the previously reported activity, however, is consistent with the extract's overall activity.…”
Section: Table 3 Continuedmentioning
confidence: 69%
“…Then it was filtrated and extracted on rota vapour. 14 Acute toxicity test of other studies found 200 mg/ Kg of Tecomalla bark extract to be the safe dose. 15 All experimental animals were divided into four groups.…”
Section: Methodsmentioning
confidence: 97%